Magyarország belső gyarmatosítása - Miklóssy, Endre (Tér és Társadalom, 1990)
A well-known feature of state socialist national economy is its lack of cost-sensitivity. More precisely, this stands, first of all, for externalities: the key actors of economic life tend to charge the „second fiddlers" with the extra costs of forced growth. As a matter of fact, all individuals, all activities, all fields and settlements which do not fall in the „mainstream" of the centralizing policy, are second fiddlers. The major instrument of charging extra costs with secondary actors is the mechanism of „spatial pump". The objective is to increase the relative profit of protagonists and decrease their relative costs at the expense of others. Obviously, this is only possible by political and economic pressure that stabilizes the quasi-colonial dependence of „ peripheries". Examples for the means of profit-increasing: gap between the relative prices of agricultural and industrial products, subsidized production, and the system of industrial branch-plants. Examples for cost-decreasing: central redistribution named as „development policy" including housing projects, institutional concentrations and financial dispreferencies. The ideology of underdeveloping peripheries is expressed by „rephasing", i.e. postponing the tasks. Besides the persisting system of interests in centralization, growing general expenses of the national economy themselves are now increasingly in the way of financing a real catching-up development. Finally, the general decline of peripheries questions reckonable economic results. There is no other solution to the problem than making externalities internal, í.e. costsensitivity.